Virtualisasi Pembelajaran melalui Integrasi Spatial Data Science Untuk Meningkatkan Geokapabilitas Mahasiswa PPG IPS - Purwanto, Purwanto; Sukriono, Didik; Hudiyanto, Reza; Elvada, Erisa; Yusuf, Alfariz Maulana; Israni, Mayang Eka (Cetta: Jurnal Ilmu Pendidikan, 2025)
The development of virtual technology encourages the innovation of learning media that is more interactive and contextual. The limitation of existing learning media in integrating spatial aspects creates an opportunity to develop media that meets learning needs. The objective of this research is to develop virtual learning media integrated with Spatial Data Science to enhance the geocapability of students in the Social Sciences Teacher Professional Program (PPG IPS). The development was carried out by utilizing Microsoft Power BI as a virtual dashboard development application capable of visualizing spatial data. The research employed a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through three main types of instruments: validation sheets, a closed user trial questionnaire, and a user response questionnaire. Validation sheets were addressed to material, language, and media experts to obtain feasibility scores, comments, and suggestions for product improvement before the trial. The user trial questionnaire consisted of a closed multiple-choice questionnaire using a Likert scale and a user response questionnaire.The collected data were analyzed using quantitative analysis and qualitative analysis techniques. Quantitative data, which contained feasibility scores, were presented in tables, while qualitative data were presented through descriptive narratives. The research findings indicate that the developed learning media obtained an "excellent" feasibility score from both experts and users. Direct classroom implementation has not yet been carried out, so its effectiveness cannot be measured. Further research is recommended to test the media's implementation in a real learning situation to obtain a more comprehensive picture of its impact on improving the geocapability of PPG IPS students.